Team identity in youth soccer: The role of coaches' feedback patterns and use of humour - Hoigaard, R.; Haugen, T.; Johansen, B. T.; Giske, R. (International Journal of Sports Science & Coaching, 2017)
The purpose of this study was to empirically examine the relationship between coaches' communication patterns (feedback and use of humour) and team identity in youth soccer. A cross-sectional design was used and participants were 532 soccer players, aged from 13 to 20 years, taking part in a youth soccer tournament, the Sør Cup. Structural Equation Modelling based multiple regression analysis was conducted, and the findings revealed that positive/instructive feedback and coaches' use of humour were positive significant predictors of team identity. Contrary to our expectations, negative/punishment feedback was not significantly related to team identity. The findings are discussed within a social identity framework. It is concluded that positive/instructive feedback and the use of humour are elements that coaches may use to develop the team identity. However, future work is needed to further validate the scales used in this study, and to examine how the use of humour may influence the athlete and the team. ABSTRACT FROM AUTHOR